The Role of National Human Rights Mechanisms for Reporting and Follow-Up (Nmrf): Understanding These New Global Domestic Processes Using the Cases of Georgia And Portugal As A Focus - Sarkin, Jeremy (Teisė, 2019)
This article reviews domestic human rights institutions called Mechanisms for Reporting and Follow-Up (NMRFs). The article scrutinizes how important state reporting on human rights has become, and then evaluates what NMRFs are, and what the different models of NRMFs are. The article focuses on the nations of Georgia and Portugal.